Overproduction of the poly(ADP-ribose) polymerase DNA-binding domain blocks alkylation-induced DNA repair synthesis in mammalian cells. - Molinete, M (1993)
The zinc-finger DNA-binding domain (DBD) of poly (ADP-ribose) polymerase (PARP, EC 2.4.2.30) specifically recognizes DNA strand breaks induced by various DNA-damaging agents in eukaryotes. This, in turn, triggers the synthesis of polymers of ADP-ribose linked to nuclear proteins during DNA repair. The 46 kDa DBD of human PARP, and several derivatives thereof mutated in its first or second zinc-finger, were overproduced in Escherichia coli, in CV-1 monkey cells or in human fibroblasts to study their DNA-binding properties, the trans-dominant inhibition of resident PARP activity, and the consequences on DNA repair, respectively. A positive correlation was found between the in vitro DNA-binding capacity of the recombinant DBD polypeptides and their inhibitory effect on PARP activity stimulated by the alkylating agent N-methyl-N'-nitro-N-nitrosoguanidine (MNNG). Furthermore, overproduced wild-type DBD blocked unscheduled DNA synthesis induced in living cells by MNNG treatment, but not that induced by UV irradiation. These results define a critical role for the second zinc-finger of PARP for DNA single-stranded break binding and furthermore underscore the importance for PARP to act as a critical regulatory component in the repair of DNA damage induced by alkylating agents.